HUBUNGAN TINGKAT PENDIDIKAN DENGAN KECEMASAN KELUARGA PASIEN DALAM MENGHADAPI PERAWATAN DI RUANG ICU RUMAH SAKIT UMUM DAERAH UNIT SWADANA PARE - Astutik, Wahyu Sri; Widodo, Yonathan (Jurnal AKP, 2011)
Intensive Care Unit is a health care unit for patients with a reversible, emergency or intermediate health problem. Because of the separate between patient and family, they need psychosocial supports. Family may experience fear and hopeless while they standing beside the patients. The objective of the research was to identify the relationship between the level of formal education and the level of anxiety of the family when they facing health care on intensive care unit of Pare Public Hospital. The research design was cross sectional. Population of the study was all patientâs family who accompanied the patient on ICU RSUD Pare, sampling was choose by researcher according to the judgment of the researcher with sample size 30 respondents. Variable of the study was formal educational level as independent variable; and the level of family anxiety as dependent variable. Research instrument was Hamilton Anxiety Rating Scale (HARS).Result of the study showed that according to Gamma test, the correlation of both variable was -0,70 by significance level (p) 0,005 less than 0,05, mean that there was significant correlation between both variable. According to the result of study, itâs suggested for health care institution/health care personals to perform health education by clear and true information for the patient and his family